Chrysanthemum indicum and chrysanthemum morifolium: chemical composition of their essential oils and their potential use as natural preservatives with antimicrobial and antioxidant activities - Youssef, Fadia S.; Eid, Safaa Yehia; Alshammari, Elham; Ashour, Mohamed L.; Wink, Michael; Readi, Mahmoud Zaki el (Foods, 2020)
The composition of essential oils of Chrysanthemum indicum and C. morifolium were comparatively studied using both Gas Chromatography/Flame ionization Detector (GC/FID) and Gas Chromatography/Mass spectrometry (GC/MS) analyses. The antiviral activity was determined using a plaque reduction assay against three common viruses namely, herpes simplex type-1 (HSV-1), hepatitis A (HAV) and vesicular stomatitis virus (VSV). The antimicrobial activity was assessed using agar diffusion and microdilution methods and the minimum inhibitory concentration (MIC) values were determined. In addition, the anti-mycobacterial evaluation was carried out using the Alamar blue assay and the effect against Helicobacter pylori was investigated. The anti-trypanosomal activity was evaluated using the resazurin method. GC investigations revealed that camphor is the major constituent of both oils accounting for 36.69 and 14.56% in the essential oils from C. indicum and C. morifolium, respectively. C. indicum was biologically more active in all experiments; it exhibited a notable antitrypanosomal activity with an IC50 value equals 45.89 μg/mL and a notable antimicrobial activity versus Streptococcus agalactiae with a MIC value of 62.5 μg/mL. It also inhibited the replication of VSV with an IC50 value of 3.14 μg/mL. Both oils revealed antioxidant potential with IC50 values of 2.21 and 2.59 mg/mL for C. indicum and C. morifolium, respectively. This study provides evidence beyond the traditional use of both Chrysanthemum indicum and C. morifolium as anti-infective agents. Thus they could be used as spices in food and can be incorporated in different food products and pharmaceutical preparations as natural preservatives possessing antioxidant potential.